ANALISIS KOMPARATIF FILSAFAT PENDIDIKAN KONSTRUKTIVISME DAN PRAGMATISME DALAM MEMAHAMI MATERI SEJARAH KEBUDAYAAN ISLAM - Ilham Saibani; Kasful Anwar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the comparison between the philosophies of constructivism and pragmatism in understanding Islamic Cultural History materials. The philosophy of constructivism emphasizes that knowledge is actively constructed by students through experience and interaction in the learning process, while pragmatism focuses on the usefulness of knowledge and its application in everyday life. This study used a qualitative method with a library research approach. The data were obtained from various sources such as books, scientific journals, articles, and other references relevant to the research topic. The data analysis technique was carried out descriptively and analytically through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that constructivism focuses more on developing critical thinking skills, understanding historical concepts, and students’ active participation in constructing knowledge about Islamic Cultural History. Meanwhile, pragmatism emphasizes contextual learning, direct experience, and the application of Islamic historical values in real life. The similarity between the two philosophies lies in their orientation toward student-centered learning, while the differences can be seen in their objectives and approaches to acquiring knowledge. Therefore, the application of these two educational philosophies can provide a positive contribution to improving students’ understanding of Islamic Cultural History materials in a critical, applicable, and meaningful way. Keywords: constructivism, pragmatism, educational philosophy, Islamic Cultural History.